Assessment of Radical Scavenging and Sickling Inhibitory Activities of the Bark of Disthemonanthus Benthamianus (Caesalpiniaceae) - Joël, Akakpo-Akue; Marcel, Ahon Gnamien; Kangah Mireille , Kplé Tatiana; Yvette, Fofié; Sanogo, Ibrahime; Claire Chiyae, Yapo-Crezoit Antoinette; Koffi Mathieu, Kra Adou (European Scientific Journal, ESJ, 2021)
Among the medicinal plants used in the treatment of sickle cell disease in south-east of Côte d'Ivoire is Disthemonanthus benthamianus. This paper focuses on assessing its antioxidant properties and its antisickling activity. The test of inhibition of sodium metabisulfite-induced sickling of the erythrocytes was carried out based on this evaluation. The total phenolic compounds contents were 45 ± 0.64 and 39.84 ± 0.69 mg/g of dry weight for ethanolic extract and the decocted respectively. The DPPH reduction test showed that the decocted (9 μg/mL) had a lower IC50 than the ethanolic extract (16 μg/mL). There was no significant difference between the sickling inhibitory activities of the ethanolic extract (87.00%) and the decocted (81.66%). This study showed that both extracts had sickling inhibitory and antioxidant activities.